O aprendizado em química nuclear no Pronatec mediado pela teoria da atividade de Engeström - Basso, Larissa Jung (2017)
Discussions regarding the importance of optimal performances in workers in all areas are growing, in the sense that they should carry out their jobs in a more effective way with interdisciplinary working skills. Nuclear Chemistry is one of these areas of modern knowledge which involve interrelated concepts in chemistry, physics, biology and mathematics to solve actual contextualized problems, giving a more completed and dynamical understanding of nuclear energy and the working processes of tools and equipment. In order to assess the learning conditions necessary to accomplish this, it was investigated what methodological contributions from the Engeströn´s Theory of Activity can be provided in teaching nuclear chemistry, through the planning and implementation of diversified teaching sequences in a PRONATEC Technical in Chemical Analysis in the Cenecista Institute of Superior Learning in Santo Angelo (IESA). This sequency is focused on the constructivist learning approach, experimental activities, analysis of educational movies and standard theoretical lectures within the Theory of Activity of Engeströn. Our results have shown that students who follow the proposed methodology do present better performance in conceptual tests in comparison with control groups A and B which receive traditional high school teacher-mediated activities and a formal acess to quantum and molecular physics with an university level which are the main prerequisites to learn nuclear physics. The use of Bloom´s Taxonomy not only allows visualizing levels of learning, self-organization and the systematic of class objectives but creates new possibilities to explore chemistry subjects in an interdisciplinar manner. In these groups of students, questionnaires of interestes and professional behavior have been collected in order to learn the way the students think about the subjects and their relationships with the general physics and physical chemistry. Futhermore, this study provided discussions that can contribute to teacher formation in Nuclear Chemistry and raised issues that allow teachers to carry out their work in a more effective way in this modern field. Using the Activity Theory and Bloom´s Taxonomy allow the teacher to ellaborate ways for the students to show the desired cognitive development through the proposed series of well-structured experiments.